2013
DOI: 10.1080/10962247.2013.795919
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and diurnal analysis of NO2 concentrations from a long-duration study conducted in Las Vegas, Nevada

Abstract: Population exposures to traffic emissions near roads have led to heightened public health concerns and awareness of the long-term levels and variability of these air pollutants. Epidemiological studies have lead to improved understanding of the associated risks and health effects of near road air pollutant emissions. While short-term studies provide insights on near-road air quality, longer-term trends need to be understood, especially for reactive pollutants such as NO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 13 publications
7
26
0
Order By: Relevance
“…To our knowledge, the only near road air quality studies using a long-term curbside station have been conducted outside of North America and primarily within European Union countries with different fuel use and vehicle fleets than U.S. cities. Near-road air quality research in the U.S has provided critical data about the spatial extent of traffic-related pollution surrounding highways, emission factors under real-world driving conditions, and the contribution of in-car exposure to total exposure using mobile measurements made within the roadway (Cho et al, 2009;Clements et al, 2009;Fruin et al, 2008;Kimbrough et al, 2013;Richmond-Bryant et al, 2009;Zhang et al, 2004;Zhu et al, 2004). This study uses long-term curbside monitoring (1 year) to assess the magnitude and temporal characteristics of roadside traffic-related pollution alongside a heavily-trafficked arterial that accommodates pedestrians, transit users, cyclists, schools, businesses, and homes at the road edge of a major arterial in Portland, Oregon.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the only near road air quality studies using a long-term curbside station have been conducted outside of North America and primarily within European Union countries with different fuel use and vehicle fleets than U.S. cities. Near-road air quality research in the U.S has provided critical data about the spatial extent of traffic-related pollution surrounding highways, emission factors under real-world driving conditions, and the contribution of in-car exposure to total exposure using mobile measurements made within the roadway (Cho et al, 2009;Clements et al, 2009;Fruin et al, 2008;Kimbrough et al, 2013;Richmond-Bryant et al, 2009;Zhang et al, 2004;Zhu et al, 2004). This study uses long-term curbside monitoring (1 year) to assess the magnitude and temporal characteristics of roadside traffic-related pollution alongside a heavily-trafficked arterial that accommodates pedestrians, transit users, cyclists, schools, businesses, and homes at the road edge of a major arterial in Portland, Oregon.…”
Section: Introductionmentioning
confidence: 99%
“…This includes understanding the contribution of these facilities to the spatial and temporal variability of this micro-environment, as well as PM concentrations and key species, such as black carbon (BC) [4,7]. Numerous studies have shown elevated levels of air pollutants adjacent to major transportation facilities [8][9][10][11][12][13][14][15][16][17]. Reported health effects from these environments include exacerbation of asthma, as well as cardiovascular and non-asthma respiratory symptoms [4].…”
Section: Environmental and Health Impacts From Transportation Sourcesmentioning
confidence: 99%
“…With the growth of coastal communities comes air management challenges (Gamas et al, 2015). Local ambient air quality is impacted by the volume of emissions from industry, transportation, and residential activities, as well as meteorological and seasonal changes (Fiore et al, 2015;Kimbrough et al, 2013). Coastal zones are also subject to land-sea breezes (LSBs), caused by the diurnal differential heating/cooling of the sea and land (Crosman and Horel, 2010;Cuxart et al, 2014;Tsai et al, 2011).…”
Section: Coastal Urban Centersmentioning
confidence: 99%